2014
DOI: 10.1248/cpb.c13-00851
|View full text |Cite
|
Sign up to set email alerts
|

New Nitrogenous Bisabolene-Type Sesquiterpenes from a Formosan Sponge <i>Axinyssa</i> sp.

Abstract: Key words sponge; Axinyssa sp.; bisabolene-type; cytotoxicity Studies in the chemistry of marine natural products, the marine sponges have emerged as one of the most prolific sources for discovery of novel secondary metabolites.1) Previous chemical investigations on sponges of the genus Axinyssa (order Halichondrida, family Halichondriidae) have led to the isolation and identification of various sesquiterpenes containing unusual nitrogenous functional groups as an isocyano, isothiocyanate, thiocyanate, bisabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…[ 87 ]. Recently, axinysaline A ( Bi20 ) and axinysaline B ( Bi19 ) were found in an unidentified Formosan sponge of the genus Axinyssa by Liu et al [ 88 ].…”
Section: Marine Isonitriles and Related Compoundsmentioning
confidence: 99%
“…[ 87 ]. Recently, axinysaline A ( Bi20 ) and axinysaline B ( Bi19 ) were found in an unidentified Formosan sponge of the genus Axinyssa by Liu et al [ 88 ].…”
Section: Marine Isonitriles and Related Compoundsmentioning
confidence: 99%
“…Sesquiterpenes with amine and isocyanate substituents were isolated from marine sponges Halichondria sp. 1) and Ciocalypta sp., 2) and other nitrogenous sesquiterpenes with formamide, [3][4][5] isonitrile, 6) isothiocyanate, 5,7) and urea 7) have been isolated from marine sponges of the genus Axinyssa. Recently, we also isolated a new rearranged nitrogenous bisabolene-type sesquiterpene, halichonic acid (2), with a novel 3-azabicyclo [3.3.1] nonene skeleton from Halichondria sp.…”
Section: Introductionmentioning
confidence: 99%
“…These bisabolene derivatives contain unique nitrogenous functional groups, such as an isothiocyanate, isonitrile, and formamide either at C-3 or C-7 of the bisabolene frameworks. They exhibit a broad range of biological activities including cytotoxicity [6,8], antimicrobial activity [6], and antifouling activity [13]. The biosynthetic pathways of these nitrogenous sesquiterpenes have attracted much attention, and incorporation experiments indicated that the precursor of the isonitrile group was either inorganic cyanide [14,15] or amino acids associated with the metabolism of tetrahydrofolate [16].…”
Section: Introductionmentioning
confidence: 99%